Women outperform men in verbal episodic memory even in oldest-old age: 13-year longitudinal results of the AgeCoDe/AgeQualiDe Study - Golchert, Johannes; Röhr, Susanne; Luck, Tobias; Wagner, Michael; Fuchs, Angela; Wiese, Birgitt; van den Bussche, Hendrik; Brettschneider, Christian; Werle, Jochen; Bickel, Horst; Pentzek, Michael; Oey, Anke; et al. (Journal of Alzheimer's disease, 2019)
Background: Sex differences in verbal episodic memory function have been widely reported. However, sex-specific effects on rates of episodic memory decline remain controversial, and evidence is particularly scarce in the oldest-old population. Object We aimed to investigate sex differences in trajectories of episodic memory performance in oldest-old individuals. Methods:Based on 13-year longitudinal data with 9 follow-up assessments of a large sample of cognitively unimpaired old (75+) primary care patients (n=3,254) participating in the German AgeCoDe/AgeQualiDe study, we used linear mixed effects analyses to model sex-specific trajectories of change in verbal episodic memory while accounting for covarying factors. Results:We found that even in the highest age group women outperformed men in immediate (b=–1.71, p<0.001) and delayed (b=–0.85, p<0.001) free recall conditions. Associated late-life trajectories, however, did not differ significantly between the sexes. We further demonstrated that younger age, higher education, and an absence of depressive symptoms predicted better performance in both sexes. In contrast, past occurrences of stroke and APOE ɛ4 carrier status showed a negative relation to test scores. Conclusion:Our findings confirm previous research suggesting that women perform better in verbal episodic memory tests. We add that this advantage is still present in the oldest-old age groups. Our results indicate that sociodemographic and health related factors are as important as genetically based APOE ɛ4 carrier status in the prediction of normal cognitive development in advanced old age.
Gesehen am 05.03.2020